2017
DOI: 10.1159/000475439
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Additional Susceptibility Loci for Inflammatory Bowel Disease in a Chinese Populationy

Abstract: Background/Aims: To investigate the associations between the rs1250569 (zinc finger MIZ-type containing 1, ZMIZ1), rs1042522 (tumour protein p53, TP53), and rs10114470 (tumour necrosis factor-like cytokine 1A, TL1A) polymorphisms and the development of inflammatory bowel disease (IBD) in a Chinese (Han) population. We analysed the expression of genes that predispose patients to Crohn’s disease (CD) and ulcerative colitis (UC). Methods: A total of 381 IBD patients and 517 healthy controls were recruited into ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Anti‐TNF treatment diminishes intestinal TL1A expression in CD patients, which is in agreement with a recent study that reported regulation of TL1A expression in CD through mucosa‐derived factors including TNF . Associations between TL1A gene polymorphism and development of CD in European, Korean, Japanese, and Chinese populations have been assessed by several Genome Wide Association Studies (GWAS) and in sum strengthen the role of TL1A as driver of inflammatory bowel diseases (IBD) . Remarkably, the link between TL1A gene polymorphisms and CD was confirmed in different ethnical groups and in patients of almost all ages, which distinguishes TL1A from a variety of other genes associated with CD.…”
Section: Dr3 In Chronic Inflammatory Diseasesupporting
confidence: 88%
“…Anti‐TNF treatment diminishes intestinal TL1A expression in CD patients, which is in agreement with a recent study that reported regulation of TL1A expression in CD through mucosa‐derived factors including TNF . Associations between TL1A gene polymorphism and development of CD in European, Korean, Japanese, and Chinese populations have been assessed by several Genome Wide Association Studies (GWAS) and in sum strengthen the role of TL1A as driver of inflammatory bowel diseases (IBD) . Remarkably, the link between TL1A gene polymorphisms and CD was confirmed in different ethnical groups and in patients of almost all ages, which distinguishes TL1A from a variety of other genes associated with CD.…”
Section: Dr3 In Chronic Inflammatory Diseasesupporting
confidence: 88%
“…Lan et al demonstrated no significant association between rs1250569 and rs1042522 genotypes and Crohn's disease (CD) or UC susceptibility. However, the frequency of allele A of rs1250569 was much higher in CD patients than that in healthy controls in a Chinese population (Lan et al, ). Li et al showed a significantly decreased frequency of the TT genotype in rs3810936 in acute anterior uveitis patients (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also proposed that certain Tnfsf15 alleles may bear prognostic value for the severity of IBD. In the Chinese population, the T allele of SNP rs10114470 was associated with increased probability of developing stricturing, penetrating, or perianal complications (27). In the same notion, Pernat Dobrez et al identified the SNP rs4263839 as a possible marker for disease progression.…”
Section: Tnfsf15 Polymorphisms Affect Susceptibility To Intestinal DImentioning
confidence: 99%